A morphology-based radiological image segmentation approach for efficient screening of COVID-19. (August 2021) - Chakraborty, Shouvik; Mali, Kalyani
Highlights: A morphology-based radiological image segmentation approach is proposed. The proposed approach can be used as a tool for early screening the suspected COVID-19 infected patients using CT images. The proposed approach exploits the advantages of simple morphological operations to effectively process spatial information. Experiments are carried out using various cluster validity indices to test the efficiency The obtained results are encouraging so that it can be adapted as a tool to combat the spread of COVID-19 disease. Abstract: Computer-aided radiological image interpretation systems can be helpful to reshape the overall workflow of the COVID-19 diagnosis process. This article describes an unsupervised CT scan image segmentation approach. This approach begins by performing a morphological reconstruction operation that is useful to remove the effect of the external disturbances on the infected regions and to locate different regions of interest precisely. The optimal size of the structuring element is selected using the Edge Content-based contrast matrix approach. After performing the opening by using the morphological reconstruction operation, further noise is eliminated using the closing-based morphological reconstruction operation. The original pixel space is restored and the obtained image is divided into some non-overlapping smaller blocks and the mean intensity value for each block is computed that is used as the local threshold value for the binarization purpose. It is preferable to manually determine the range of the infected region. If a region is greater than the upper bound then that region will be considered as an exceptional region and processed separately. Three standard metrics MSE, PSNR, and SSIM are used to quantify the outcomes. Both quantitative and qualitative comparisons prove the efficiency and real-life adaptability of this approach. The proposed approach is evaluated with the help of 400 different images and on average, the proposed approach achieves MSE 307.1888625, PSNR 23.7246505, and SSIM 0.831718459. Moreover, the comparative study shows that the proposed approach outperforms some of the standard methods and obtained results are encouraging to support the battle against the COVID-19.